2010
DOI: 10.1126/scisignal.2001140
|View full text |Cite
|
Sign up to set email alerts
|

Signaling from the Endoplasmic Reticulum Activates Brassinosteroid Signaling and Promotes Acclimation to Stress in Arabidopsis

Abstract: The ability to acclimate to stresses enables plants to grow and develop under adverse environmental conditions. Regulated intramembrane proteolysis (RIP) triggered by endoplasmic reticulum (ER) stress mediates some forms of stress signaling. Brassinosteroids (BRs) have been implicated in plant adaptation to stress, but no mechanisms for activation have been discovered. Here, we reveal a connection between ER stress signaling and BR-mediated growth and stress acclimation. Arabidopsis transcription factors bZIP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
211
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(213 citation statements)
references
References 54 publications
1
211
1
Order By: Relevance
“…Since the discovery of bZIP60, two other stress-induced, membrane-associated TFs have been described in Arabidopsis, AtbZIP17, which responds to UPR agents, heat, and salt stress (20,22) and AtbZIP28 that is activated by UPR agents and heat (21,22,31). Both of these factors are activated conventionally in a manner similar to the activation of ATF6.…”
Section: Arabidopsis Bzip60mentioning
confidence: 99%
See 2 more Smart Citations
“…Since the discovery of bZIP60, two other stress-induced, membrane-associated TFs have been described in Arabidopsis, AtbZIP17, which responds to UPR agents, heat, and salt stress (20,22) and AtbZIP28 that is activated by UPR agents and heat (21,22,31). Both of these factors are activated conventionally in a manner similar to the activation of ATF6.…”
Section: Arabidopsis Bzip60mentioning
confidence: 99%
“…In response to stress, bZIP60 appears in an active, truncated form seemingly to have undergone proteolytic processing similar to AtbZIP17 and AtbZIP28 (20)(21)(22). However, the mechanism for the presumed proteolysis event is not understood, because the C-terminal tail of bZIP60 does not have a canonical S1P cleavage site and its activation does not require S1P or S2P (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The precise chloroplast localization of EGY1 and S2P2 still remains unknown (Zybailov et al 2008;Chen et al 2005). The protein encoded by the AT4G20310 gene has been demonstrated to be directed to the Golgi membrane (Che et al 2010). The localization of EGY3 proteins remains unconfirmed, but AramLocCon predicts localization of this protein in the chloroplast (Schwacke et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it was demonstrated that activated forms of AtbZIP17 and AtbZIP28 can also regulate genes involved in the brassinosteroid signaling pathway, thereby identifying a point of integration between ER stress response and growth and development pathways. 14 Previously characterized MTTFs that belong to the NAC family have also been shown to be involved in stress response but also regulate developmental processes in Arabidopsis. NTM1 was one of the first MTTFs to be characterized in Arabidopsis and was shown to mainly regulate genes involved in cell division through interactions with cytokinins.…”
mentioning
confidence: 99%